Heterogeneous Organocatalysts Based on a Triazine‐Triazole Silane Ligand. Issue 38 (4th October 2018) - Cruz, Paula; Pérez, Yolanda; del Hierro, Isabel
Abstract: Invited for the cover of this issue is Isabel delàHierro from Universidad Rey Juan Carlos, Madrid, Spain. The cover image shows the hexagonal and worm‐like mesoporous structure of the ordered organic‐inorganic hybrid materials reported. Abstract : Research is our daily exciting adventure… Read more about the story behind the cover in the Cover Profile and about the research itself in theP. Cruz, Y. Pérez, and I. del Hierro .